Current status, spatial features, health risks, and potential driving factors of soil heavy metal pollution in China at province level. (November 2020) - Hu, Bifeng; Shao, Shuai; Ni, Hao; Fu, Zhiyi; Hu, Linshu; Zhou, Yin; Min, Xiaoxiao; She, Shufeng; Chen, Songchao; Huang, Mingxiang; Zhou, Lianqing; Li, Yan; et al.
Abstract: In this study we systematically reviewed 1203 research papers published between 2008 and 2018 in China and recorded related data on eight kinds of soil heavy metals (Cr, Pb, Cd, Hg, As, Cu, Zn, and Ni). Based on that, the pollution levels, ecological risk and health risk caused by soil heavy metals were evaluated and the pollution hot spots and potential driving factors of different heavy metals in different provinces were also identified. Results indicated accumulation of heavy metals in soils of most provinces in China compared with background values. Consistent with previous findings, the most prevalent polluted heavy metals were Cd and Hg. Polluted regions are mainly located in central, southern and southwestern China. Hunan, Guangxi, Yunnan, and Guangdong provinces were the most polluted provinces. For the potential health risk caused by heavy metals pollution, children are more likely confront with non-carcinogenic risk than adults and seniors. And children in Hunan and Guangxi province were experiencing relatively larger non-carcinogenic risk. In addition, children in part of provinces were undergoing potentially carcinogenic risks due to soil heavy metals exposure. Furthermore, in our study the 31 provinces in mainland China were divided into six subsets according to corresponding potential driving factors for heavy metal accumulation. Our study provide more comprehensive and updated information for contributing to better soil management, soil remediation, and soil contamination control in China. Graphical abstract: Image 1 Highlights: Cd and Hg were the most polluted heavy metals in soil across China. The ER values for Cd in 30 provinces varied from moderate to very high risk. Hunan, Guangxi, Yunnan and Guangdong were confirmed as priority control provinces. Children are undergo larger health risk than adults and seniors in China. Controlling factors of heavy metals accumulation in different provinces were mapped.